Emergency drills for agricultural drought response: A case study in Guatemala - Müller, A; Mora, V.; Rojas, E.; Díaz, J.; Fuentes, O; Grion, E.; Gayaan, A.; Etten, Jacob van (Wiley, 2019)
Drills are an important element of disaster management, helping to increase preparedness and reduce the risk of real‐time failure. Yet, they are not applied systematically to slow‐onset disasters such as a drought, which causes damage that is not instantly apparent and thus does not solicit immediate action. This case study evaluates how drills inform institutional responses to slow‐onset disasters. It spotlights Guatemala, a country where drought has severe impacts on livelihoods and the food security of small farmers. By implementing part of the Ministry of Agriculture, Livestock and Food's institutional response plan for drought, it explores how drills can help to detect issues in emergency response and to foster an institutional focus on improvements in preparedness. The results reveal that drills alone do not trigger institutional improvements if unsupported by a wider strategy that seeks to enhance capacities and protocols. These findings are valuable, however, in making problems transparent and in creating the space for discussion.